Venous thromboembolism in 13 Indonesian patients undergoing major orthopedic surgery (Faculty of Medicine Universitas Indonesia, 2009)
Aim To estimate the incidence of VTE in Indonesian patients undergoing major orthopedic surgery and not receiving thromboprophylaxis. Methods This was an open clinical study of consecutive Indonesian patients undergoing major orthopedic surgery, conducted in 3 centers in Jakarta. Bilateral venography was performed between days 5 and 8 after surgery to detect the asymptomatic and to confirm the symptomatic VTE. These patients were followed up to one month after surgery. Results A total of 17 eligible patients were studied, which a median age of 69 years and 76.5% were females. Sixteen out of the 17 patients (94.1%) underwent hip fracture surgery (HFS). The median time from injury to surgery was 23 days (range 2 to 197 days), the median duration of surgery was 90 minutes (range 60 to 255 minutes), and the median duration of immobilization was 3 days (range 1 to 44 days). Thirteen out of the 17 patients were willing to undergo contrast venography. A symptomatic VTE was found in 9 patients (69.2%) at hospital discharge. Symptomatic VTE was found in 3 patients (23.1%), all corresponding to clinical signs of DVT and none with clinical sign of PE. These patients were treated initially with a low molecular weight heparin, followed by warfarin. Sudden death did not occur up to hospital discharge. From hospital discharge until 1-month follow-up, there were no additional cases of symptomatic VTE. No sudden death, bleeding complication, nor re-hospitalization was found in the present study. Conclusion The incidence of asymptomatic (69.2%) and symptomatic (23.1%) VTE after major orthopedic surgery without thromboprophylaxis in Indonesian patients (SMART and AIDA), and still higher than the results of the Western studies. A larger study is required to establish the true incidence, and more importantly, that the use of thromboprophylaxis in these patients is warranted. (Med J Indones 2009; 18: 249-56)